Investigating and grounding the over time comparability of the substantive units used in the Greek Household Budget Surveys - Oikonomaki, Maria (The Greek Review of Social Research, 2022)
The investigation of the over time (and cross-national) comparability of sample survey data is a prerequisite for data analysis. In this context, the paper discusses over time comparability of the substantive units for the Greek Household Budget Surveys conducted from 1957/1958 to 2020. The findings show that, the use of more detailed and restrictive common definitions for the household and its members were applied in the more recent surveys, ensuring comparability of concepts. The introduction of a reference person indicates a shift in the definition from gender-role oriented responsibilities to economic criteria that poses as a cut-off point the year that was first employed for the overtime comparability of the data. This methodological study contributes to the growing research on the over time comparability of sample survey data that is used extensively in social research.